Social work with Latinos a cultural assets paradigm - Delgado, Melvin (Oxford : Oxford University Press, 2007)
Presents a definition and demographic map of Latinos, Latino culture, and a cultural asset paradigm. This book identifies strategies for designing culturally relevant programs and services. It provides an understanding on culture, access assets, and how they intersect to inform practices. It is intended for students and professionals.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hispanic Americans -- Services for; Social work with minorities -- United States; Hispanic Americans -- Social conditions